IMPLEMENTASI PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII3 SMP NEGERI 26 MAKASSAR - Febryanti Febryanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
This inquiry was classroom action research which aimed at improving mathematics learning achievement through implementation of the portofolio-based instruction. The research subjects were 38 Grade VIII students of SMP Negeri 26 Makassar in academic year 2007/2008. The research was conducted within two cycles covering the process of: a) preparation of the action, b) implementation of the action within the first and the second cycles, c) conduction observation of the lessons within the two cycles, d) conducting evaluation at the end of each cycle, e) analyzing the data of the evaluation and of the observation, and f) conducting reflection based upon the results of the data analysis. The data were gathered using learning achievement tests and an observation checklist. The data were analyzed using both qualitative and quantitative data analyses. After implementing the portofolio-based instruction, the result were: within the first cycle, for the first aspect of portfolio, the average score of the students’ learning achievement was 61.78 of an ideal score 100 with standar deviation 8.54; the percentage of the attainment of the learning achievement was 31.57% (12 out of 38 students achieved the mastery learning level); for the second aspect of the portofolio, the average score of the students’ learning achievement was 67.13 of an ideal score 100 with standard deviation 12.80; the percentage of the attainment of the learning achievement was 57.89%(22 out of 38 students achieved the mastery learning level) and for the third aspect of the portfolio, the average score of the students’ learning achievement was 55.15 of an ideal score 100 with standard deviation 12.88; the percentage of the attainment of the learning achievement was 34.21%(13 out of 38 students achieved the mastery learning level).